2011 Florida Plant Disease Management Guide: Apple (Malus domestica) - Mathews L. Paret; Tim Momol; Laura Ritchie; Hank Dankers (EDIS)
This updated 13-page fact sheet from the 2011 Florida Plant Disease Management Guide highlights several common diseases affecting apples in Florida and includes short list of fungicides approved for disease management of apple in Florida. Written by Mathews L. Paret, Tim Momol, Laura Ritchie, and Hank Dankers, and published by the UF Department of Plant Pathology, July 2011. (photo courtesy of Clemson University - USDA Cooperative Extension Slide Series, Bugwood.org)